Measuring the Self-Reliance of Refugees. (13th April 2020) - Leeson, Kellie; Bhandari, Prem B; Myers, Anna; Buscher, Dale
Abstract: How do we know whether a refugee household is self-reliant if this is not measured? Although self-reliance has been promoted as a critical assistance strategy for refugees in recent years, there have been limited attempts to rigorously measure the concept. This field report introduces a new measurement tool to assess the movement toward self-reliance among refugee households. The development and utility of a tool to measure self-reliance are described using the pilot studies conducted in Ecuador, Egypt and Lebanon over a 9- to 18-month period. This report utilized unique panel data from 167 refugee households in Egypt and 94 households in Ecuador. The panel data was collected at two points in time (baseline and endline) using paper and pencil or Open Data Kit forms on tablets during face-to-face interviews. This panel group was used to perform the change analysis to examine the movement of households along a self-reliance continuum. Findings show that, overall, 59.8% of households in Ecuador and 64.7% of households in Egypt moved upward in composite score in self-reliance while less than 30% of households regressed in both countries. Further examination is needed to refine and evaluate the tool. The results provide an important starting point and insights into measuring self-reliance using simple indicators and an opportunity to reframe assistance around self-reliance, neither of which had previously been a focus of refugee assistance or relevant literature. It is believed that this methodology will be of use to academics and practitioners seeking to study refugee self-reliance around the world.